2009
DOI: 10.1002/cne.22186
|View full text |Cite
|
Sign up to set email alerts
|

SynCAM1 expression correlates with restoration of central synapses on spinal motoneurons after two different models of peripheral nerve injury

Abstract: SynCAM1 and neuroligins (NLGs) are adhesion molecules that govern synapse formation in vitro. In vivo, the molecules are expressed during synaptogenesis, and altered NLG function is linked to synapse dysfunction in autism. Less is known about SynCAM1 and NLGs in adult synapse remodeling. CNS synapse elimination occurs after peripheral nerve injury, which causes a transient decrease in synapse number on spinal motoneurons. Here we have studied the expression of SynCAM1 and NLGs in relation to changes in synapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 44 publications
5
21
0
Order By: Relevance
“…1g-i, l). From earlier studies [8], we know that the maximal extent of synaptic stripping is reached at 14 days after axotomy, a time point when NGL-2 mRNA levels have started increasing.…”
Section: Results Mrna Expression Of Netrin G-2 Ligand In the Uninjurementioning
confidence: 97%
See 2 more Smart Citations
“…1g-i, l). From earlier studies [8], we know that the maximal extent of synaptic stripping is reached at 14 days after axotomy, a time point when NGL-2 mRNA levels have started increasing.…”
Section: Results Mrna Expression Of Netrin G-2 Ligand In the Uninjurementioning
confidence: 97%
“…For instance, SynCAM and neuroligins (NLGs) are able to induce synapse formation in various assays and NLG-deficient mice display altered synaptic function [3][4][5][6][7]. Recently we showed that axotomized spinal motoneurons change their expression of SynCAM1, and NLG-2 and NLG-3 during synaptic detachment and restoration after peripheral nerve injury [8]. Whether SynCAM1 and NLGs are the only synaptic adhesion molecules affected by axotomy in spinal motoneurons is not known.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Initial observations [33], [34], [35], [36] were used to suggest that processes of reactive astrocytes and/or microglia, which proliferate and surround axotomized motoneurons, might play an important role, but based on the results of more recent studies [37], a shift in attention to axotomy induced changes in the motoneurons has occurred. In particular, the decline in production of cell adhesion molecules by axotomized motoneurons has been shown to precede the actual withdrawal of synapses [20], [36], [38], [39], suggesting that, in intact animals, these molecules are part of an active, retrograde signaling mechanism that promotes synapse retention. In addition, immune system-related molecules, such as the major histocompatibility complex (MHC) class I molecules [39] and members of the complement family [40] have been associated with synaptic withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable, therefore, to postulate that the breakage of this adhesive binding could be a preliminary step that antecedes synapse disassembly in axotomized motoneurons. In a series of related studies, it has been found that axotomy induces rapid down-regulation of the mRNAs encoding for the CAMs neuroligin-2, neuroligin-3, netrin G-2 ligand, netrin G-3 ligand, and SynCAM1 in motoneurons, as well as a more gradual decrease in the level of PSD-95 mRNA expression (Zelano et al, 2007(Zelano et al, , 2009Berg et al, 2010). The long-term expression analysis further showed that these changes were reversed following regeneration, in parallel with the restoration of afferent synaptic inputs to the motoneurons.…”
Section: Removal Of Central Synaptic Inputs To Motoneurons Following mentioning
confidence: 99%